Archaean Geochemistry : The Origin and Evolution of the Archaean Continental Crust - Kroner, A. (Springer-Verlag, 2017)
Mantle Chemistry and Accretion History of the Earth; Geochemical Characteristics of Archaean Ultramafic and Mafic Volcanic Rocks: Implications for Mantle Composition and Evolution; ...